Design of Low-Frequency acGIC Voltage Stability Laboratory Protocol - Sithebe, Ngcebo S (Department of Electrical Engineering, 2023)
Geomagnetically Induced Currents (GICs) are formed as a direct consequence of space weather phenomena and have detrimental effects on power systems. GICs enter the power system through transformers' grounded neutrals, causing an array of problems ranging from transformer overheating to voltage instability. There have been extensive studies on the effects of GICs, particularly on power transformers as they are the power systems' most susceptible components to GICs. The effects on transformers then affect the rest of the power system and may lead to voltage instability and blackouts. Recent studies have shown that a real GIC is not necessarily a dc as it has been previously modelled in literature. In reality, GICs are multi-frequency, multi-amplitude currents. At the same time, voltage stability analysis due to GICs with low frequency ac as a GIC representative has not been explored in detail in the literature. This dissertation assesses the effects of GICs on the voltage stability of power systems using a low-frequency ac (acGIC) model as a GIC representative. This is different from the conventional dc model (dcGIC). A laboratory and simulation protocol using a frequency-dependent transmission line with resistive and inductive elements in each phase, and a novel low-frequency ac injection circuit was designed and tested. This single frequency, single amplitude acGIC injection circuit is a first approximation of the real signal GIC. The effects and differences in the response of the power system to dc and low-frequency ac injections are explored and presented. The implementation of the protocol in the laboratory and simulation environments showed that there is a fundamental difference in the response of the power system when subjected to ac injection compared to dc injection. The research showed that the dc model for GIC is a worst-case scenario, constantly at the ‘prospective GIC. Contrarily, low-frequency ac model for GIC is constantly changing, never reaching the prospective GIC and, therefore, the extreme dc settling point. This study shows that with a low-frequency ac model, though being a first approximation, the network parameter response is not constant and the effect of the GIC on the network parameters varies with respect to the magnitude of the GIC at an instance. Furthermore, the implications on voltage stability revealed that the loadability effect on the system due to GIC is also not constant as the dc model depicts. It is, however, dependent on the current flow of GIC at a particular instance during a geomagnetic storm. This research showed that for better power systems modelling with GIC, a varying current injection is necessary to fully understand the effects on the system.